The Steel European Stock Market Efficiency - Viorica Chirila; Ciprian Chirila (CES Working Papers, 2015)
Testing the hypothesis of informational efficiency is a permanent preoccupation of researchers because the theories and the models of modern finance are based on it. This paper presents the results obtained after testing the efficiency hypothesis, in the weak form, for the European stock market of the companies that belong to the economic steel sub-sector. Following the use of both linear and non-linear tests of autocorrelation of returns we can conclude that the European stock market in the economic steel sub-sector is inefficient from an informational point of view and the investors in these stocks may obtain better results than those of the European market in general.
Keywords: G15; C58; 330; steel & iron subsector; stock; return; BDS test; Runs test